Serotonergic System and Its Role in Epilepsy and Neuropathic Pain Treatment: A Review Based on Receptor Ligands - Panczyk, Katarzyna; Golda, Sylwia; Waszkielewicz, Anna; Zelaszczyk, Dorota; Gunia-Krzyzak, Agnieszka; Marona, Henryk (Current Pharmaceutical Design, 2015)
The serotonergic system is involved in pathomechanisms of both epilepsy and neuropathic pain. So far, participation in the epileptogenesis and maintenance of epilepsy was proved for 5-HT1A, 5-HT2C, 5-HT3, 5-HT4 and 5-HT7 receptors as well as 5-HTT serotonin transporter. Depending on the receptor type or its localization, its stimulation may increase or decrease neuronal excitability. According to the available data, neuropathic pain mechanisms involve 5-HT1A/1B/1D, 5-HT2A/2B/2C, 5-HT3, 5-HT4, 5-HT6 5-HT7 receptors and 5-HTT serotonin transporter. Changes in their expression modulate pain mainly by affecting the transmission through serotonergic descending pathways. Several compounds, whose mechanisms of action base on influence on the serotonergic system, are already in use. These are 5-HT3 agonists (triptans) in case of migraine, tricyclic antidepressants or monoamine reuptake inhibitors in neuropathic pain treatment. In addition, selective and non-selective ligands are tested for their anticonvulsant or analgesic properties. Some ED50 values have been already obtained in such animal models as maximal electroshock (MES)-induced seizures (epilepsy), spinal nerve ligation (SNL), chronic constriction injury (CCI) or formalin (neuropathic pain). This review shows that in case of drug discovery within the serotonergic system one must take into account special significance of factors such as: the species, the type of model, the route of administration, and the dose range.
Keywords: 5-HT